Observations on nematodes in vineyards in the Western Cape Province, with special reference to the genera Xiphinema and Longidorus - Smith, P. C.(Peter Clifford) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1967.